STUDY ON THE THERMAL-MECHANICAL COUPLING CHARACTERISTICS OF DISC BRAKE UNDER DRAG AND START-STOP BREAKING MODES - YUAN Qiong; LI ShiSheng (Jixie qiangdu)
A three-dimensional thermal-mechanical coupling finite element model of disc brake is established,and the thermal-mechanical coupling characteristics and friction-induced vibration characteristics in two modes: drag braking and startstop braking is studied,in addition,the influence of different deceleration behaviors on thermal-mechanical coupling and vibration characteristics in start-stop braking mode is discussed. Results show that: under the effect of thermal-mechanical coupling,the thermal deformation forms of the brake pad on both sides of the disc are completely different,resulting in significant differences in the temperature distribution of the friction discs on both sides. As the temperature increases,the vibration intensity of the brake system gradually decreases. Due to the difference in temperature leads to the difference in thermal deformation level on both sides of the brake disc. Therefore,the vibration intensity of the brake piston side is greater than that of the finger side.The deceleration behavior of the brake disc has a significant influence on the thermal-mechanical coupling characteristics and friction-induced vibration characteristics of the system. In the fast braking mode,the heat exchange between the brake and the outside environment is significant,the interface temperature is low but the vibration intensity is large. In the slow braking and step braking modes,the interface temperature increases rapidly,but the vibration intensity of the system is low due to the slow friction process. Especially in the case of step-by-step braking,the vibration intensity at a certain stage may be very weak. These results have certain guiding significance for understanding the temperature distribution characteristics of brake system and improving the brake vibration noise.